(untitled) (The Review of Diabetic Studies, 2025)
Background: Anterior cruciate ligament (ACL) injury is a common condition that results in significant functional impairment and delayed return to physical activity. The optimal timing for initiating rehabilitation following ACL injury or reconstruction remains controversial, despite growing evidence supporting early physical therapy. Aim: This research aimed to conduct a systematic review and meta-analysis to assess the effect of early against delayed initiation of physical therapy on functional recovery, return to sport, and quadriceps muscle strength following ACL injury or reconstruction. Methods: A systematic review and meta-analysis have been done in line with PRISMA guidelines. PubMed, Web of Science, Cochrane Library, and Scopus have been searched for eligible studies published up to 2025. Randomized controlled trials and observational researches comparing early and delayed initiation of physical therapy or rehabilitation in patients with ACL injury or reconstruction were included. Information has been examined utilizing Review Manager (RevMan) version 5.4.1. Mean difference with ninety-five percent confidence intervals (CI) was determined for continuous results, and a fixed- or random-effects model was applied depending on the level of heterogeneity. Main Findings: Nine studies published between 2010 and 2025 have been involved in the qualitative synthesis, and three researches were eligible for quantitative meta-analysis for each outcome. Functional outcome scores (IKDC/Lysholm) were significantly elevated in the early rehabilitation group compared with the delayed rehabilitation group (mean difference 1.32; ninety-five percent CI 1.00 to 1.64; p-value under 0.001), with insignificant heterogeneity (I² = 0%). Early rehabilitation was also related to a significantly shorter time to return to sport (mean difference −1.40 months; ninety-five percent CI −1.84 to −0.96; p -value under 0.001; I² = 38%). Additionally, quadriceps muscle strength was significantly greater in the early rehabilitation group (mean difference 1.44; ninety-five percent CI 1.02 to 1.85; p-value under 0.001; I² = 0%). Conclusion: Early initiation of physical therapy following ACL injury or reconstruction is associated with superior functional outcomes, earlier return to sport, and improved quadriceps muscle strength compared with delayed rehabilitation. These results support the implementation of early rehabilitation strategies as part of evidence-based management of ACL injuries. Background: Anterior cruciate ligament (ACL) injury is a common condition that results in significant functional impairment and delayed return to physical activity. The optimal timing for initiating rehabilitation following ACL injury or reconstruction remains controversial, despite growing evidence supporting early physical therapy. Aim: This research aimed to conduct a systematic review and meta-analysis to assess the effect of early against delayed initiation of physical therapy on functional recovery, return to sport, and quadriceps muscle strength following ACL injury or reconstruction. Methods: A systematic review and meta-analysis have been done in line with PRISMA guidelines. PubMed, Web of Science, Cochrane Library, and Scopus have been searched for eligible studies published up to 2025. Randomized controlled trials and observational researches comparing early and delayed initiation of physical therapy or rehabilitation in patients with ACL injury or reconstruction were included. Information has been examined utilizing Review Manager (RevMan) version 5.4.1. Mean difference with ninety-five percent confidence intervals (CI) was determined for continuous results, and a fixed- or random-effects model was applied depending on the level of heterogeneity. Main Findings: Nine studies published between 2010 and 2025 have been involved in the qualitative synthesis, and three researches were eligible for quantitative meta-analysis for each outcome. Functional outcome scores (IKDC/Lysholm) were significantly elevated in the early rehabilitation group compared with the delayed rehabilitation group (mean difference 1.32; ninety-five percent CI 1.00 to 1.64; p-value under 0.001), with insignificant heterogeneity (I² = 0%). Early rehabilitation was also related to a significantly shorter time to return to sport (mean difference −1.40 months; ninety-five percent CI −1.84 to −0.96; p -value under 0.001; I² = 38%). Additionally, quadriceps muscle strength was significantly greater in the early rehabilitation group (mean difference 1.44; ninety-five percent CI 1.02 to 1.85; p-value under 0.001; I² = 0%). Conclusion: Early initiation of physical therapy following ACL injury or reconstruction is associated with superior functional outcomes, earlier return to sport, and improved quadriceps muscle strength compared with delayed rehabilitation. These results support the implementation of early rehabilitation strategies as part of evidence-based management of ACL injuries.